Homocysteine and Mitochondria in Cardiovascular and Cerebrovascular Systems - Kaplan, Peter (Int J Mol Sci, 2020)
Elevated concentration of homocysteine (Hcy) in the blood plasma, hyperhomocysteinemia (HHcy), has been implicated in various disorders, including cardiovascular and neurodegenerative diseases. Accumulating evidence indicates that pathophysiology of these diseases is linked with mitochondrial dysfunction. In this review, we discuss the current knowledge concerning the effects of HHcy on mitochondrial homeostasis, including energy metabolism, mitochondrial apoptotic pathway, and mitochondrial dynamics. The recent studies suggest that the interaction between Hcy and mitochondria is complex, and reactive oxygen species (ROS) are possible mediators of Hcy effects. We focus on mechanisms contributing to HHcy-associated oxidative stress, such as sources of ROS generation and alterations in antioxidant defense resulting from altered gene expression and post-translational modifications of proteins. Moreover, we discuss some recent findings suggesting that HHcy may have beneficial effects on mitochondrial ROS homeostasis and antioxidant defense. A better understanding of complex mechanisms through which Hcy affects mitochondrial functions could contribute to the development of more specific therapeutic strategies targeted at HHcy-associated disorders.